2013
DOI: 10.1016/j.aml.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear microscale interactions in the kinetic theory of active particles

Abstract: The aim of this note is to examine the sources of nonlinearity arising in the kinetic theory of active particles. We show how nonlinearities enter the different terms of the theory, giving rise to possible developments toward the modeling of different types of complex systems, mainly living and social ones, where proliferative–destructive processes must be included. Finally, some research perspectives are discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The random walker (RW) method (see [51]) is a segmentation method based on a "path distance". It belongs to the classes of probabilistic methods, that allow to address several scientific tasks, such as optimization problems via Consensus-Based Optimization [62], Opinion Formation [63] or Particle Swarm Optimization [64]. More precisely, the RW method works as follows: in each image there are subregions of pixels which are marked with labels.…”
Section: The Random Walker Methodsmentioning
confidence: 99%
“…The random walker (RW) method (see [51]) is a segmentation method based on a "path distance". It belongs to the classes of probabilistic methods, that allow to address several scientific tasks, such as optimization problems via Consensus-Based Optimization [62], Opinion Formation [63] or Particle Swarm Optimization [64]. More precisely, the RW method works as follows: in each image there are subregions of pixels which are marked with labels.…”
Section: The Random Walker Methodsmentioning
confidence: 99%
“…Therefore N is the total number of tweets posted during the day 1 + 3( − 1) and N = L =1 N = 699 450 is the sample size. Inside each cluster the sentiment associated to each message is driven by a reinforcement mechanism, that can be modelled by means of a GRP urn: the probability to have a tweet with positive sentiment is increasing with the number of past tweets with positive sentiment and the reinforcement is mostly driven by the most recent tweets, in the sense explained in Section 2 (conversely, a particle interacting approach to study opinion formation may be found in [8,10,11]). In Fig.…”
Section: Covid-19 Epidemic Twitter Analysismentioning
confidence: 99%
“…Some important examples include biophysics, where these techniques are involved in the observation of molecular level motion of kinesin in microtubules and of motion of myosin on actin [52], in the study of the infection path of a virus [49] or in the investigation of cytoskeletal filaments [1]; another topic involving particles tracking problem regards the observation of protein motion in cell membranes [37] or intracellular transport [32]. Other interesting areas of application include statistical mechanics [5,6], fluid dynamics and mechanics, in particular rheology [34], where the thermal motion of Brownian particles has been tracked to study local rheological properties [20], complex fluids [2,47] and microrheology in medicine [23]. Colloidal works have benefited from developments in particle tracking procedures in measuring biofluids such as mucus [48] and vitreous humor [50].…”
mentioning
confidence: 99%